Implementasi Manajemen Pendidikan Berbasis Total Quality Manajemen - Kurniawan, Wakib; Maulidin, Syarif; Rohman, Miftahur (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2024)
The implementation of Education Management at Bustanul Ulum Jayasakti Islamic Boarding School based on Total Quality Management (TQM) is an important innovative step in improving education standards in the institution. This study aims to describe and analyze how the quality assurance of Islamic boarding schools using the TQM approach has developed. This effort involves all relevant parties to achieve the vision and mission of Bustanul Ulum Jayasakti Islamic Boarding School. The research method used is a case study with a qualitative approach. Data were collected through interviews, observations, and documentation, and their validity was checked through triangulation and increased researcher diligence. Data analysis was conducted using the Miles and Huberman interactive model. The results show that although there are efforts to improve the quality of education by implementing TQM, its implementation has not been fully equitable. The main focus is mainly on improving the curriculum, while other aspects of TQM are still less structured. The role of the leader is crucial in mobilizing and empowering the team to ensure the quality of the pesantren in accordance with TQM principles and with proper managerial skills. In addition, participation in monitoring every activity is also considered important to meet the needs of stakeholders in education, such as students, representatives or parents, as well as the surrounding community.